A New Viewpoint to Schema Modes and Mode Domains Through Polyvagal Theory: Could Schema Modes Be Just a Way of Coping? - Karaosmanoğlu, Hasan Alp; ATEŞ, NİDA; Köse Karaca, Bahar; Aytaç, Mert (Springer, 2022)
The aim of this study is to investigate how the schema modes defined in Schema Theory group together and accordingly question the conceptualization of schema modes considering the theories combining evolutionary, neuroscientific, and psychological point of views in psychology literature. It was hypothesized that there would be differences in the categorization and conceptualization of schema modes conceptualized by Schema Theory based on Polyvagal Theory. The sample of the study consists of 2032 participants aged between 18 and 71 years old (M = 36.00, SD = 14.312) who applied to a psychotherapy center in Istanbul working with the approach of Schema Therapy. Short Schema Mode Inventory was applied to the participants. According to the results of the second-order factor analysis, compliant surrenderer, healthy adult, punitive parent, happy child, and detached protector modes were clustered in the first factor. Impulsive child, enraged child, condescending, and easily bored child modes were loaded under the second factor while demanding parent, detached self-soother, and status-seeking modes were loaded under the third factor. When the results were evaluated with respect to Polyvagal Theory, it was determined that the first factor represented the parasympathetic nervous system activation and consisted of schema modes that include surrender, freezing, and socialization responses while the second factor consisting of schema modes related to flight or fight responses represented the sympathetic nervous system activation. Moreover, the third factor consisted of the schema modes of the sympathetic nervous system, which included flight or fight responses with parasympathetic inhibition (vagal brake). The results were discussed in line with the literature.
Keywords: Schema Therapy; Schema Modes; Polyvagal Theory; Schema Theory